Peran Lembaga Pengawas dalam Memberikan Pelindungan Data Pribadi Anak Ditinjau Menurut Perbandingan Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi dan Personal Information Protection Act 2011 Korea Selatan - Sevina Aullia Putri; Sinta Dewi Rosadi; Betty Rubiati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The rapid development of digital technology has a significant impact on people's lives, including children's lives. Due to the use of this technology, protecting children's personal data has become an important issue in the current digital era, where children are vulnerable to the misuse of their personal data. The aim of this research is to examine the role of supervisory institutions in providing protection for children's personal data in Indonesia and to analyze it in comparison with the Personal Information Protection Act (PIPA) in South Korea. This research employs a normative legal approach. The legal materials used in this study focus on primary legal sources in the form of legislation, secondary legal sources such as literature, books, and journals, tertiary legal sources including Black’s Law Dictionary and the Indonesian Language Dictionary, as well as legal comparisons between Indonesia and South Korea. The results of this study indicate that the law in Indonesia has not fully provided adequate protection for personal data, particularly regarding the establishment and role of supervisory institutions, which have not yet been formed as a means of safeguarding children's personal data. In contrast, the regulations in South Korea provide more detailed provisions regarding the protection of children's personal data, along with an effectively functioning supervisory body known as the Personal Information Protection Commission (PIPC).